Endothelial Dysfunction and Extra-Articular Neurological Manifestations in Rheumatoid Arthritis - Jessica Maiuolo; Carolina Muscoli; Micaela Gliozzi; Vincenzo Musolino; Cristina Carresi; Sara Paone; Sara Ilari; Rocco Mollace; Ernesto Palma; Vincenzo Mollace (Biomolecules, 2021)
Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory autoimmune disease that affects about 1% of the global population, with a female–male ratio of 3:1. RA preferably affects the joints, with consequent joint swelling and deformities followed by ankylosis. However, evidence has accumulated showing that patients suffering from RA can also develop extra-articular manifestations, including cardiovascular disease states, neuropathies, and multiorgan dysfunction. In particular, peripheral nerve disorders showed a consistent impact in the course of the disease (prevalence about 20%) mostly associated to vasculitis of the nerve vessels leading to vascular ischemia, axonal degeneration, and neuronal demyelination. The pathophysiological basis of this RA-associated microvascular disease, which leads to impairment of assonal functionality, is still to be better clarified. However, endothelial dysfunction and alterations of the so-called brain-nerve barrier (BNB) seem to play a fundamental role. This review aims to assess the potential mechanisms underlying the impairment of endothelial cell functionality in the development of RA and to identify the role of dysfunctional endothelium as a causative mechanism of extra-articular manifestation of RA. On the other hand, the potential impact of lifestyle and nutritional interventions targeting the maintenance of endothelial cell integrity in patients with RA will be discussed as a potential option when approaching therapeutic solutions in the course of the disease.